2022
DOI: 10.3390/app12136606
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Eco-Friendly Concrete Nano-Change with Eggshell Powder

Abstract: One of the unifying factors for all countries is the large consumption of chicken, and other, eggs in food and other types of economic activity. After using various types of eggs for their intended purpose, a large amount of waste accumulates in the form of eggshells. Currently, this problem exists and needs a non-trivial, original solution. The aim of the work was to fill the scientific gap in the direction of studying the microstructure formation of improved nano-modified environmentally-friendly concrete ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Technological and testing equipment and measuring instruments were used the same as in [ 52 , 53 , 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Technological and testing equipment and measuring instruments were used the same as in [ 52 , 53 , 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, some studies reported a reduction in strength when cement is replaced with high percentages of ESP, especially above 10%. Furthermore, with high ESP dosage, the modulus of elasticity is also decreased [17][18][19]. Thus, the optimum percentage of ESP recommended is only 10% to 15%, whether in concrete, cement mortar, reinforced concrete, or clay brick applications [20].…”
Section: Introductionmentioning
confidence: 99%
“…This is a record value that exceeded the values of previous years (419 ppm for 2021 and 417 ppm for 2020) [ 6 ]. Several studies have been devoted to solving a similar problem—the disposal of agricultural, industrial waste, fuel, and energy complex in concrete, but at the same time in concrete based on cement [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. At the same time, it should be noted that geopolymer concretes are even more promising, environmentally friendly, and economical due to the absence of clinker binders in them and the use of more environmentally friendly cheap components in their composition, which can significantly approach the implementation of the global environmental agenda.…”
Section: Introductionmentioning
confidence: 99%